Pan-genome analysis of the R2R3-MYB genes family in Brassica napus unveils phylogenetic divergence and expression profiles under hormone and abiotic stress treatments - Fan, Haiyan; Li, Jiawei; Huang, Wencong; Liang, Aoshuang; Jing, Liqing; Li, Jintao; Yang, Qing-Yong; Liu, Kede; Yang, Zhiquan (Frontiers in Plant Science, 2025)
IntroductionThe R2R3-MYB transcription factors (TFs) are pivotal regulators of plant growth, development, and stress responses. However, their genetic diversity and functional roles in Brassica napus remain underexplored at a pan-genome scale.MethodsWe identified R2R3-MYB genes in 18 published rapeseed genomes and analyzed their genomic distribution patterns, gene duplication, selective pressure, gene structure, conserved motifs, and phylogenetic relationships using a pan-genome approach. Additionally, transcriptomic datasets from hormone treatments and drought/heat stress experiments were analyzed to identify hormone-responsive and stress-responsive genes.ResultsWe systematically identified 7,552 R2R3-MYB genes from 18 B. napus genomes, which were grouped into 353 gene clusters based on the pan-genome approach, including 139 core, 121 softcore, 68 dispensable, and 25 private gene clusters. Similar to Arabidopsis, the B. napus R2R3-MYB genes can be clustered into 29 subgroups based on the phylogenetic tree, suggesting conserved functional roles in B. napus and A. thaliana. Cis-element profiling highlighted enrichment in hormone-responsive and stress-related elements in the promoter regions of the R2R3-MYB genes. Transcriptomic analyses identified 283 hormone-responsive and 266 stress-responsive R2R3-MYB genes, and 30 co-regulated genes under drought and heat stress implicate their roles in combined stress adaptation.DiscussionThese findings provide the first pan-genome resource for R2R3-MYB genes in B. napus, which can serve as pivotal targets for enhancing stress resilience in rapeseed breeding programs.